Potensi Tanaman Sorgum (Sorghum bicolor L.), Azotobacter sp. dan Pseudomonas sp. Sebagai agen biologis dalam proses Fitoremediasi Hidrokarbon minyak bumi - Pujawati Suryatmana; Alyani Shabrina; Nadia Nuraniya Kamaluddin; Betty Natalie Fitriatin; Reginawanti Hindersah; Mieke Rochimi Setiawati (Fakultas Pertanian Universitas Padjadjaran, 2020)
Phytoremediation using Sorghum (Sorghum bicolor L.) plant is an alternative green technology to overcome oil polluted soil. Improving of the phytoremediation performance are needed stimulating agent to enhance the rate of hydrocarbon biodegradation and increase the plant growth. One of the bioagent that can act as biostimulant is Azotobacter sp. and Pseudomonas sp., because thouse bioagent can provide elements N and P, and phytohormone for sorghum plants. The purpose of this study is to examine the role of Azotobacter sp. and Pseudomonas sp. as a biostimulant for Sorghum bicolor L. in the process of biodegradation of petroleum hydrocarbon in soil system. The factorial randomized block design was used as the experimental design. The treatment consisted of 4 application levels of Azotobacter sp. and 4 levels of application of Pseudomonas sp. The results showed that there was no interaction between Azotobacter sp. and Pseudomonas sp. aplication on the efficiency of hydrocarbon degradation of the population of Azotobacrer spp., Pseudomonas spp. and plant height increase. Azotobacter sp. and Pseudomonas sp. also did not show an increase in value on each test variable. While, the potential of sorghum plants without the application of Azotobacter sp. and Pseudomonas sp. (control treatment) showed the value of the efficiency of biodegradation in the range of values of 60.442% - 68.165% during 14 weeks period and not significantly different from other treatments.